Pengaruh Motivasi Terhadap Kepuasan Kerja dan Dampaknya Terhadap Kinerja Akuntan Pendidik (Dosen Akuntansi) (Studi pada Perguruan Tinggi Swasta di Bandar Lampung) - . Irwandi (Jurnal Akuntansi dan Keuangan, 2016)
The purpose of this study is to analyze the effect of motivation to the job satisfaction. And analyze the effect of motivation, and job satisfaction to the performance of accountanting educator at private universities in Bandar lampung. This research used explanatory survey method and were analized by descriptive and verification test. The data was collected by distributing questionare to 41 educated accountanr of perguruan tinggi swasta in Bandar lampung. The Structural Equation Model based on Partial Least Square (PLS) was used to measure the impact of exogenous variables on endogenous variables directly and indirectly in this research. Based on this research, it was found that 1) motivation influenced significantly and positively to the job satisfaction. 2) motivation did not influence indirectly to the lecturer performance but it influenced significantly and positively to the lecturer performance indirectly pass through job satisfaction. 3) job satisfaction as intervening variable influenced significantly and positively to the accounting lecturer performance.